System analysis/operations research techniques in agricultural engineering - Bardaie, Mohd Zohadie; Haith, Douglas A. (Penerbit Universiti Pertanian Malaysia, 1981)
System analysis in an analytical tool which has been used extensively in the business industry, financial institutions, government agencies and military operations. Its use in these sector of the economy has given much benefit in increasing their efficiencies and productivities. However, the agricultural industry, specifically the agricultural engineering sector, is not making the most of this analytical tool. The potential for its use in agricultural engineering is very promising. This paper will present a brief discussion of the systems analysis approach. Some of the problems in agricultural engineering which have been analysed using the systems analysis techniques will be high-lighted. An example application of the approach for the problem of soil salinity in irrigation project planning will be presented.